A bibliometric analysis of strabismus (from 2004 to 2023) - Yanghui Xiu; Yanghui Xiu; Yanghui Xiu; Yanghui Xiu; Yanghui Xiu; Yanghui Xiu; Yanghui Xiu; Yujie Zhang; Yujie Zhang; Yujie Zhang; Yujie Zhang; Yujie Zhang; et al. (Frontiers in Medicine)
Over the past two decades, strabismus research has evolved significantly, driven by innovations in AI-assisted diagnostics, minimally invasive surgical techniques, and a heightened focus on psychosocial outcomes and systemic disease linkages. This bibliometric analysis of 4,515 articles from the Web of Science Core Collection (2004–2023) maps global research trends, identifying the United States of America (USA), China, and the United Kingdom (UK) as leading contributors. A keyword co-occurrence analysis highlights a shift toward innovative treatments, including non-surgical interventions, and highlights the growing interest in interdisciplinary approaches that integrate clinical practice with psychological and social dimensions of strabismus. In conclusion, this bibliometric review provides a comprehensive overview of current strabismus research and identifies key areas for further investigation, serving as a valuable resource for researchers and clinicians aiming to advance the field.